Perencanaan Pembangunan Daerah Partisipatif: Upaya Penyempurnaan Proses dan Hasil Musrenbang, Studi Kasus Dinas PUPR Kota Payakumbuh - Br Barus, Ernawati; Dito Meliala, Harry (Jurnal Administrasi Publik dan Pemerintahan, 2024)
The Relationship between Mastery of Meaning Relations and the Ability to Use Sentences of Class X of Berastagi Private Vocational High School, Berastagi District, Karo Regency. This study aims to describe the mastery of meaning relations and the ability to use sentences in the aspects of using synonyms, antonyms, homonyms, homophones, homographs, hyponyms, and polysemy. In addition, it also aims to describe the relationship between mastery of meaning relations and the ability to use sentences of Grade X students of SMK Swasta Bersama Berastagi Kecamatan Berastagi Kabupaten Karo. Data were obtained from 84 grade X students, with an objective test instrument. Through the descriptive method, data were processed using the Product Moment correlation formula:  Based on the formula above, the following research results were obtained: The mastery of meaning relations of class X students of SMK Swasta Bersama Berastagi Kecamatan Berastagi Kabupaten Karo is categorized as B (good) with an average value of 71.19; The ability to use sentences of class X students of SMK Swasta Bersama Berastagi Kecamatan Berastagi Kabupaten Karo is categorized as B (good) with an average value of 70.77; The relationship between mastery of meaning relations and the ability to use sentences is positive and the relationship between the two variables is sufficient/moderate with a correlation index of 0.454; The higher the mastery of meaning relations of students, the better the students' ability to use sentences.